(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Cancer is a serious health issue that remains a top cause of mortality across the globe. Anticancer medications have been developed as we have understood the molecular mechanism that leads to cancer genesis has grown. Chemically produced medications, on the other hand, have had little impact on overall survival rates during the last several decades. As a result, to improve the efficacy of conventional therapies of cancer, new approaches and revolutionary chemoprevention drugs are necessary. Phytochemicals are those molecules that occur naturally in plants, are important resources for developing new medicines and may also be used to treat cancer. Only a few example include taxol analogues, vinca alkaloids such as vinblastine vincristine and, and podophyllotoxin analogues. These phytochemical generally work by interfering with molecular pathways connected to cancer formation and progress. Some of the distinct approaches include increased antioxidants status, carcinogen inactivation, reducing its rapid growth, promotion of cell cycle arrest and death, and immune system regulation. The main goal of this study is to summarise what we now know about natural product active chemicals, including their pharmacology and molecular or particular targets. The most recent advancements and limitations in the development of phytochemical-based anticancer therapies are also discussed. The author wants to boost phytochemicals research not just for its scientific worth, but also for its medicine development potential. As a result, anticancer phytochemicals that have been studied in preclinical and clinical settings have gotten a lot of attention.